PENGARUH IKLIM ORGANISASI DAN KOMITMEN ORGANISASITERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PERAWAT (STUDI PADA PERAWAT RSIA ERIA BUNDA PEKANBARU) - Agustina Purba; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the effect organizational climate and organizational commitment on work oganizational citizenship behavior (ocb) nurses at RSIA Eria Bunda Pekanbaru. It was proposed two indenpendent variables and one dependent variable, namely organizatinal climate and organizational commitment as indenpendent variables and oganizational citizenship behavior (ocb) as a dependen variable. This research methods are descriptive and quantitative by using SPSS 21, where the sample used is nurses at RSIA Eria Bunda Pekanbaru with 71 respondents. To take the sample, the writer used cencus method. Technique of collecting data was through questionnarie and interview.The result ofanalysis using the validity test, reability test, determination test, simple linear regression test, multiple linear regression test, t test, and f test. As the result, it can be seen that both the organizational climate have significant on oganizational citizenship behavior (ocb), that organizational commitment have significan effec on oganizational citizenship behavior (ocb). Organizational climate and organizational commitment have a significan effec on oganizational citizenship behavior (ocb).Keywords: Organizational Climate, Organizational Commitment, and Oganizational Citizenship behavior.